Analisis Dampak COVID-19 dan Faktor-Faktor yang Mempengaruhi Indeks Saham Bank Jatim Menggunakan Pendekatan Regresi Time Series - Muktar Redy Susila; Mochamad Jamil; Bambang Hadi Santoso (Department of Mathematics, Universitas Negeri Gorontalo, 2022)
Stock is one of the instruments that can be used to invest. The factors suspected of influencing the fluctuations in the stock price index are the Jakarta Composite Index (JCI), the rupiah exchange rate, and the Covid-19. The purpose of this study is to analyze the effect of the JCI, the rupiah exchange rate, and the Covid-19 on the Jatim Bank stock price index. To analyze the effect of the JCI, the rupiah exchange rate, and the Covid-19 on the Jatim Bank stock price index, time series regression analysis was used. The results of the analysis show that the JCI, the rupiah exchange rate, and the Covid-19 have a significant effect on the Jatim Bank stock price index. The p-value of the three variables is less than 0.05. The value of the determination coefficient is 65.56%, so that the diversity of the dependent variable that can be explained by the model is 65.56%.